2014
DOI: 10.1080/10888691.2014.983031
|View full text |Cite
|
Sign up to set email alerts
|

Family Background, School-Age Trajectories of Activity Participation, and Academic Achievement at the Start of High School

Abstract: Applying latent class and regression techniques to data from the NICHD Study of Early Child Care and Youth Development (n = 997), this study explored the potential academic advantages of time spent in out-of-school activities. Of particular interest was how these potential advantages played out in relation to the timing and duration of activity participation and the family contexts in which it occurred. Participation closer to the start of high school—including consistent participants and latecomers—was associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…A growing number of studies have analyzed panel data with at least one or two lagged time points of previous achievement (Covay and Carbonaro 2010;Crosnoe et al 2015;Fredricks 2012;Morris 2016) to address the problem of self-selection. Panel data offer an opportunity to construct models that are much better suited to estimating causal effects by exploiting the time-ordered structure of the data.…”
Section: Methodological Limitations Of Prior Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of studies have analyzed panel data with at least one or two lagged time points of previous achievement (Covay and Carbonaro 2010;Crosnoe et al 2015;Fredricks 2012;Morris 2016) to address the problem of self-selection. Panel data offer an opportunity to construct models that are much better suited to estimating causal effects by exploiting the time-ordered structure of the data.…”
Section: Methodological Limitations Of Prior Researchmentioning
confidence: 99%
“…Additionally, ECA participation has been linked to higher college attendance rates and occupational success (Gardner et al 2008;Morris 2016). The timing and consistency of ECA participation may affect academic outcomes; a study using the National Institute of Child Health and Human Development's Study of Early Child Care and Youth Development data indicated that consistent participation throughout elementary and high school and activities begun during the transition to high school had a significant relationship with academic achievement during high school (Crosnoe, Smith, and Leventhal 2015).…”
Section: Research On Eca Participation and Student Outcomesmentioning
confidence: 99%
“…Our research builds on previous studies that have identified links between participation in ECAs and a range of positive developmental outcomes. For example, in research with children and adolescents in the United States, extracurricular engagement was positively related to academic performance [7], motivation [8,9], social skills [10], and educational resilience [11], and negatively related to behavioral problems [12], and school dropout [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…There may also be differential effects of extracurricular activity participation by family income. 18 Low-income adolescents tend to reside in neighborhoods that contain fewer economic resources, community and family services, more delinquent peer groups, and higher rates of violent crime compared to other adolescents. 19 Extracurricular activity participation may protect adolescents in low-income communities from exposure to delinquent peer groups and violent neighborhoods.…”
mentioning
confidence: 99%